Acoustic Sensors: Broad Bandwidth, Self‐Powered Acoustic Sensor Created by Dynamic Near‐Field Electrospinning of Suspended, Transparent Piezoelectric Nanofiber Mesh (Small 28/2020). Issue 28 (16th July 2020) - Wang, Wenyu; Stipp, Patrick N.; Ouaras, Karim; Fathi, Saeed; Huang, Yan Yan Shery
Abstract : Most acoustic sensors are resonant systems, thus the associated sensitivity bandwidth is narrow. In article number 2000581, Yan Yan Shery Huang and co‐workers fabricate a broad bandwidth acoustic sensor, inspired by the acoustic sensing mechanism of the spider silk, by dynamic near‐field electrospinning. Composed of freely suspended piezoelectric nanofibers, the self‐powered, transparent acoustic sensor has high sensitivity throughout the majority of the audible sound spectrum at hearing‐safe loudness level.